The Desire for Children, the Children of one’s Desire. The Meaning of Medically Assisted Procreation and Technological Family Planning - Di Nicola, Paola (Italian Sociological Review, 2019)
The spread of medically assisted procreation (MAP) techniques promises to realise the previously denied human dream of planning and controlling one’s progeny. The new social imaginary features a disproportionately greater freedom of choice and decision-making powers for adults (parents), along with increased risks of genetic determination also given the extremely rapid developments in genetics. At the same time, this demand is fuelled by the presence of a booming private reproductive market which often employs commercial marketing techniques by promising couples and women not only that they can achieve their desire for a child but can make the ‘child of their desire’ – they can have the children that they want, when and how they want them. This article presents the results of an exploratory study conducted with a sample of 360 subjects aged between 25 and 45 who may or may not have not used MAP and examines their responses to a questionnaire. In particular, what lies behind the idea that technology and private fee-based services can supplant nature and public services in areas that they cannot reach? How widespread is the idea? What are the ethical, social and cultural implications at the root of the concept? How can this idea modify the sense and meaning of procreation? What level of freedom and rights should the baby be granted? The results of the research show that the sample is divided almost equally on the issue of MAP between those who acknowledge its potential but are aware of its associated social and cultural risks and those who highlight its potential by referring to rights-based reasons and money-based reasons.